Methodology for developing and evaluating food-based dietary guidelines and a Healthy Eating Index for Ethiopia: a study protocol. Issue 7 (16th July 2019) - Bekele, Tesfaye Hailu; de Vries, Jeanne JHM; Trijsburg, Laura; Feskens, Edith; Covic, Namukolo; Kennedy, Gina; Brouwer, Inge D
Abstract : Introduction: Food-based dietary guidelines (FBDGs) are used to promote and maintain healthy eating in a population, by providing country-specific guidance. However, many African countries like Ethiopia do not have FBDGs. This paper describes the methodology for the development of Ethiopian FBDGs and for creating and evaluating a Healthy Eating Index and a scoring tool that can be used to monitor the adherence of the population to FBDGs. Methods and analysis: A multidisciplinary technical working group will be tasked to develop FBDGs for the general population above 2 years of age based on identification of priority diet-related public health problems and risk factors, and a systematic review of dietary patterns in relation to the identified priority health outcomes, following a multistep process. FBDGs will be translated into daily food choices for specific subpopulations by applying linear programming using data from the National Food Consumption Survey (NFCS) of 2011. FBDGs will be evaluated for cultural appropriateness, acceptability, consumer understanding and practicality. A dietary gap assessment will be conducted by comparing the national food supply with the country's food demand. In addition an Ethiopian Healthy Eating Index (EHEI) will be developed based on the FBDGs using the NFCS data. The EHEI will be evaluated by comparing the EHEI Score based on 24 hours diet recall with that of the EHEI Score based on a Food Frequency Questionnaire, by analysing the association of the EHEI Score with population characteristics and micronutrient intake with or without additional adjustment for energy intake. Finally, a brief Food Quality Screening tool scoring for the important EHEI components will be developed to enable evaluation for counselling. Ethics and dissemination: Ethical approval is received from the Scientific and Ethical Review Office of the Ethiopian Public Health Institute. The findings will be disseminated through peer-reviewed publications.A dissemination workshop will be organised with key implementing sectors of the food system for a healthier diet (http://a4nh.cgiar.org/our-research/research-flagships/ ) and with key public and private partners. The findings from this study will be translated into FBDGs and shared through conferences, reports and the mass media (TV and radio). Trial registration number: NCT03394963 ; Pre-results.